The Impact of Interactive Flat Panel Display–Based Digital Games with a Cognitive Scaffolding Approach on the Improvement of Early Childhood Literacy and Numeracy - Ahmad Widianto; Kabul Suprayitno (Manunggal Halim Jaya, 2026)
This study aims to explore the effect of using digital games based on an Interactive Flat Panel Display (IFPD) with the application of cognitive scaffolding on early literacy and numeracy at Mutiara Hati Kindergarten. The research employed a qualitative case study approach involving the principal, teachers, and parents as subjects. Data were collected through semi-structured interviews and classroom observations and were then analyzed thematically. The results showed that the use of IFPD increased children’s interest, focus, and engagement in literacy and numeracy activities. The implementation of cognitive scaffolding by teachers was proven to help children understand letters, words, numbers, and simple operations more effectively. The children also demonstrated improved literacy and numeracy skills, both in the classroom and at home. Based on these findings, it can be concluded that the integration of interactive digital games and teacher scaffolding effectively enhances early literacy and numeracy. This study provides implications for teachers and schools to optimize the use of interactive digital media in early childhood learning.